NUTRITION CONTENT IN WINGED BEANS THAT CAN INCREASE BREAST MILK PRODUCTION - Mika Mediawati; Triatmi Andri Yanuarini (Universitas STRADA Indonesia, 2023)
A mother often has problems in exclusive breastfeeding, one of the main obstacles is milk production that is not fluent. Traditional plants that are allegedly able to facilitate breast milk, one of which is winged bean. The purpose of this study is to describe the nutritional content of winged bean. This research is a literature study using the traditional review method. Data were obtained from various literature sources by searching through the internet in the form of research results in the form of journals, articles, theses, theses, and dissertations both abroad and domestically. The results of this study are that winged bean contains complete nutrition that can increase milk production. Hormones that can increase milk production are prolactin and oxytocin hormones. The active compounds in winged bean are allegedly able to increase milk production. Winged bean may be an alternative to Galactogogue although it still needs further research